Arbejdsmarkedet er i bedring efter historisk hårdt tilbageslag - Mikkel Bess; Pernille Valentin Borgensgaard; Thea Thalia Iuel Rasmussen (Danmarks Nationalbank, 2020)
– The Danish labour market experienced a historically severe setback after the partial shutdown of the economy but is now recovering. This Economic Memo gives a detailed account of the developments on the Danish labour market over the past six months and serves as the foundation for Danmarks Nationalbank's Outlook for the Danish economy, September 2020.
Keywords: 330; Arbeitsmarkt; Arbeitsmarktstatistik; Coronavirus; Dänemark